Genetic diversity of subtype C HIV-1 env variants in peripheral blood mononuclear cell (PBMC) DNA from infected mother-child pairs : a comparison of Heteroduplex Mobility Assay (HMA) and Base Excision Sequence Scanning (BESS) methods - Loubser, A S (Division of Virology, 2015)
Includes bibliographical references.